Retinal progression biomarkers of early and intermediate age-related macular degeneration - Flores, Rita (2022)
Funding Information: Funding: This work was supported by Fundação para a Ciência e Tecnologia project PTDC/MED-PAT/30385/2017 and iNOVA4Health-UIDB/04462/2020, a program financially supported by Fun-dação para a Ciência e Tecnologia/Ministério da Educação e Ciência, Portugal, through national funds and co-funded by FEDER under the PT2020 Partnership Agreement. Funding Information: This work was supported by Fundação para a Ciência e Tecnologia project PTDC/MEDPAT/30385/2017 and iNOVA4Health-UIDB/04462/2020, a program financially supported by Fundação para a Ciência e Tecnologia/Ministério da Educação e Ciência, Portugal, through national funds and co-funded by FEDER under the PT2020 Partnership Agreement. Publisher Copyright: © 2021 by the authors. Licensee MDPI, Basel, Switzerland.